E-Agenda Simulation: Is It Effective for Improving Students’ Learning Competences and Motivation in Vocational High School? - Ismiyati Ismiyati; Adisti Eva Rahmaningrum; Mar'atus Sholikah (Faculty of Engineering, Universitas Negeri Yogyakarta, 2022)
Innovative and interesting learning should be pursued by the teacher so that students will be more motivated to learn and can get better learning outcomes. In this study, we tried to test the effectiveness of the demonstration method assisted by e-Agenda simulation video learning media on the learning competence and motivation of filing subjects. The study was conducted with a quasi-experimental y with nonequivalent control group design in SMK Negeri 1 Salatiga. There were 62 respondents in this study. Data were collected by two methods, namely tests and questionnaires. Independent sample tests were used for data analysis techniques. The findings showed that e-Agenda learning media can improve students' cognitive and psychomotor learning outcomes between students who learn to use e-Agenda learning media and students who learn to use manual agenda. We also found that e-agenda learning media influences student motivation. Thus, we concluded that the e-Agenda learning media can improve students' learning competencies and motivation. In addition, it also affects students to be more motivated to learn diligently. Future studies should explore other factors affecting media effectiveness.